2017
DOI: 10.7324/ijcrr.2017.9211
|View full text |Cite
|
Sign up to set email alerts
|

"Lignocellulose Degrading Enzymes from Fungi and Their Industrial Applications"

Abstract: The rich diversity of fungi and diverse range of enzymes produced by them together make researchers to exploit their potential for various industrial applications. Few of the fungal enzymes have already been harnessed and many other are to be explored and brought into use. Recent studies suggested that the lignin degrading fungi can be used in the bioremediation of aromatic hydrocarbons including dioxins, dibenzofuran, aromatic dyes, etc. Employing fungal enzymes for the treatment of pollutants has gained attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 67 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…These ions which are mainly produced by three pathways—cellobiose dehydrogenase catalyzed reactions, quinone redox cycling, and Fenton reactions catalyzed by glycopeptides ( Dashtban et al, 2010 ), attack the plant cell wall components including lignin governing cleavage of various bonds. It has been observed that post cleavage fragments of lignin are more susceptible to attack by diverse lignin modifying enzymes ( Kantharaj et al, 2017 ). Thus diverse fungi are more efficient in pre-treatment of lignin to their intermediates or low molecular weight heterogeneous compounds (5/6-carbon chains) ( Kumar and Chandra, 2020 ).…”
Section: Methods Of Lignin Depolymerizationmentioning
confidence: 99%
“…These ions which are mainly produced by three pathways—cellobiose dehydrogenase catalyzed reactions, quinone redox cycling, and Fenton reactions catalyzed by glycopeptides ( Dashtban et al, 2010 ), attack the plant cell wall components including lignin governing cleavage of various bonds. It has been observed that post cleavage fragments of lignin are more susceptible to attack by diverse lignin modifying enzymes ( Kantharaj et al, 2017 ). Thus diverse fungi are more efficient in pre-treatment of lignin to their intermediates or low molecular weight heterogeneous compounds (5/6-carbon chains) ( Kumar and Chandra, 2020 ).…”
Section: Methods Of Lignin Depolymerizationmentioning
confidence: 99%